2006
DOI: 10.1038/sj.npp.1301048
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Val158Met Catechol O-Methyltransferase Genetic Polymorphism with Panic Disorder

Abstract: Genetic as well as clinical data suggest that catechol O-methyltransferase (COMT) is involved in multiple complex psychiatric conditions. Recent studies have described an association between the Val158Met COMT polymorphism and panic disorder. Other recent investigations provide evidence that there are other loci within or nearby the COMT gene that may contribute to the susceptibility to panic disorder. To further evaluate the influence of the Val158Met COMT polymorphism in panic disorder we genotyped this mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 38 publications
(56 reference statements)
2
62
0
Order By: Relevance
“…This finding is the latest in a line of studies that show relationships between COMT genotype and personality traits in women but not in men. In particular, anxietyrelated phenotypes (such as harm avoidance or neuroticism) have been repeatedly (though often weakly) associated in women with the Met 158 allele (Eley et al, 2003;Enoch et al, 2003;Olsson et al, 2005;Stein et al, 2005), with similar findings in anxiety disorder (Domschke et al, 2004;Woo et al, 2004;Rothe et al, 2006). A recent meta-analysis of the panic disorder studies (Domschke et al, 2007) confirmed this sex difference, but also revealed an additional complexity, in that the relationship interacted with ethnicity such that panic disorder was associated with the Met 158 allele in Caucasian women but with the Val 158 allele in Asian women.…”
Section: Sexually Dimorphic Effects Of Comt Genotype On Psychiatric Dmentioning
confidence: 80%
“…This finding is the latest in a line of studies that show relationships between COMT genotype and personality traits in women but not in men. In particular, anxietyrelated phenotypes (such as harm avoidance or neuroticism) have been repeatedly (though often weakly) associated in women with the Met 158 allele (Eley et al, 2003;Enoch et al, 2003;Olsson et al, 2005;Stein et al, 2005), with similar findings in anxiety disorder (Domschke et al, 2004;Woo et al, 2004;Rothe et al, 2006). A recent meta-analysis of the panic disorder studies (Domschke et al, 2007) confirmed this sex difference, but also revealed an additional complexity, in that the relationship interacted with ethnicity such that panic disorder was associated with the Met 158 allele in Caucasian women but with the Val 158 allele in Asian women.…”
Section: Sexually Dimorphic Effects Of Comt Genotype On Psychiatric Dmentioning
confidence: 80%
“…Table 3 presents the main effects for 43 SNPs with a P trend < 0.05 but P trend > 0.01. Of interest is the functional nonsynonymous polymorphism catechol-O-methyltransferase (COMT) Val 158 Met involved in the dopaminergic pathway and associated with several psychiatric conditions (16), which in this study was associated with a reduced risk of colorectal cancer (OR, 0.75 and 0.58 for the heterozygote and minor allele variant, respectively).…”
Section: Opamentioning
confidence: 92%
“…Few studies have observed association of intermediate phenotypes of anxiety mainly harm avoidance [Enoch et al, 2003], low extraversion, and high neuroticism [Eley et al, 2003;Stein et al, 2005] in women with low activity Met allele. In contrast, women with phobic anxiety [McGrath et al, 2004] and panic disorder [Rothe et al, 2006] showed significant over-representation of Val allele. Women specific influence of COMT gene variation has also been reported for other loci in the gene.…”
Section: Comt (Catechol-o-methyltransferase)mentioning
confidence: 72%